Implementation of a monitoring system for students' learning paths - Ferreira, Rui Filipe Correia (2023)
New technologies revolutionized the educational system. Among those technologies, the use of learning management systems was normalized in higher education and brought a lot of possibilities to address current problems faced by students and schools, such as increasing drop-out rates, poor academic performance, and lack of motivation and engagement. In this dissertation, we look at Moodle, the learning management system used at Iscte, to find the learning path indicators that can better represent the students' learning paths to visualize and monitor them. An analysis of Moodle's architecture and of the learning path indicators is made with the aim of developing a platform to showcase those indicators. The platform consists of a real-time dashboard that extracts the information from Moodle and showcases it to the student, where the student can choose what unit course they want to visualize their learning path. The validation of the platform was performed with a questionnaire, where 24 students enrolled in higher education answered questions about their familiarity with learning management systems, as well as what they thought about the learning indicators proposed and the platform itself. Regarding their opinion on the platform, 87.5% of the participants think the platform would have a positive impact on their academic performance (20.8% strongly agree, while 66.7% agree).